2011
DOI: 10.1093/ecam/nep105
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antibacterial Activity of Punica granatum Peel Ethanol Extract against Salmonella

Abstract: Punica granatum is commonly used in Korea as a traditional medicine for the treatment of pathogenic bacteria. In this study, we investigated the in vitro and in vivo antimicrobial activity of P. granatum peel EtOH extract (PGPE) against 16 strains of Salmonella. The minimal inhibitory concentrations of PGPE were in the range of 62.5–1000 x03BCg mL−1. In addition, the in vivo antibacterial activity of the PGPE extract was examined in a S. typhimurium infection mouse model. Mice were initially infected with S. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 48 publications
5
62
0
3
Order By: Relevance
“…The methanol extract of Punica granatum fruit rind showed dermatophytic activity at low concentrations. Choi et al (2009) reported anti-salmonella activity of Punica granatum ethanol extract.…”
Section: Discussionmentioning
confidence: 99%
“…The methanol extract of Punica granatum fruit rind showed dermatophytic activity at low concentrations. Choi et al (2009) reported anti-salmonella activity of Punica granatum ethanol extract.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenol content is 25-30% in P. granatum, and 23-37% in T. chebula RETZ. 24) Their extracts have shown multiple pharmacological activities, such as antimicrobial, 8,15,25) cardiac action, antioxidant, 11,26) antitumor, 10,27,28) antiviral, 29) and the promotion of wound healing. 12,13) The intestinal tract contains the largest reservoir of bacteria and endotoxins in an animal's body.…”
Section: Discussionmentioning
confidence: 99%
“…Parekh et al mentioned that plants extracts from organic solvent have been found to give more consistent antimicrobial activity compared to water extract [29] . Recently, many research studies have been done to discover the presence of various bioactive compounds like flavonoids, tannins, phenol in fruits peels like mangosteen, pomegranate, citrus, and grape [30][31][32][33][34] . However, there are no reports available on the antibacterial activities of the tropical pumpkin.…”
Section: Discussionmentioning
confidence: 99%